2017
DOI: 10.1002/ejsp.2307
|View full text |Cite
|
Sign up to set email alerts
|

Competence and confusion: How stereotype threat can make you a bad judge of your competence

Abstract: Women tend to have competence doubts for masculine‐stereotyped domains (e.g., math), whereas men tend to think they can handle both feminine‐stereotyped and masculine‐stereotyped domains equally well. We suggest that perhaps women's more frequent experience with stereotype threat can partly explain why. Our results showed that when stereotype threat was primed in high school students (n = 244), there was no relationship between their performance on an academic test (the SweSAT) and their assessment of their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
3
0
3
Order By: Relevance
“…Esto contradice los resultados de algunas investigaciones previas que han reportado que las mujeres tienden a ser más vulnerables a la amenaza de estereotipo (Arbuthnot, 2009;Boucher et al, 2015;Brown & Josephs, 2001;Galdi et al, 2014;Good et al, 2008;Irriberi & Rey-Biel, 2017;Kenney et al, 2006;Laurin, 2016;Osborne & Walker, 2006;Pérez-Garín et al, 2017;Picho & Schmader, 2018;Picho & Stephens, 2012;Rydell et al, 2011;Schmader & Johns, 2003;Spencer et al, 1999), pero apoya los resultados de otros estudios que han mostrado que cuando los estudiantes tienen un alto autoconcepto matemático y un alto interés en este dominio pueden contrarrestar los posibles estereotipos negativos que existen en el contexto social sobre el género (Flore et al, 2019;Ganley et al, 2013;Gerstenberg et al, 2012;Harley & Sutton, 2013;Smetackova, 2015;Tellhed & Adolfsson, 2018).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Esto contradice los resultados de algunas investigaciones previas que han reportado que las mujeres tienden a ser más vulnerables a la amenaza de estereotipo (Arbuthnot, 2009;Boucher et al, 2015;Brown & Josephs, 2001;Galdi et al, 2014;Good et al, 2008;Irriberi & Rey-Biel, 2017;Kenney et al, 2006;Laurin, 2016;Osborne & Walker, 2006;Pérez-Garín et al, 2017;Picho & Schmader, 2018;Picho & Stephens, 2012;Rydell et al, 2011;Schmader & Johns, 2003;Spencer et al, 1999), pero apoya los resultados de otros estudios que han mostrado que cuando los estudiantes tienen un alto autoconcepto matemático y un alto interés en este dominio pueden contrarrestar los posibles estereotipos negativos que existen en el contexto social sobre el género (Flore et al, 2019;Ganley et al, 2013;Gerstenberg et al, 2012;Harley & Sutton, 2013;Smetackova, 2015;Tellhed & Adolfsson, 2018).…”
Section: Discussionunclassified
“…Además, no se encontraron diferencias en el desempeño de los cuatro grupos de susceptibilidad a la amenaza de estereotipo. Estos hallazgos no son congruentes con la mayoría de estudios previos, en los cuales se ha encontrado que: a) los hombres se desempeñan mejor en tareas matemáticas que las mujeres (Aguiar et al, 2011;Arias et al, 2016;Cervini & Dari, 2009;Ministerio de Educación Nacional de Colombia, 2016;Organización para la Cooperación y el Desarrollo Económicos, 2016;Schmader et al, 2008;Valdés, 2013) y b) generalmente el grupo de alta susceptibilidad a la amenaza de estereotipo y el de los no involucrados suelen presentar bajos desempeños en el área, mientras que los grupos de estudiantes con baja susceptibilidad se caracterizan por altos desempeños (Arbuthnot , 2009;Boucher et al, 2015;Brown & Pinel, 2003;Galdi et al, 2014;Good et al, 2008;Irriberi & Rey-Biel, 2017;Picho, 2016;Picho & Rojas, 2011;Picho & Schmader, 2018;Steele, 1997;Steele & Aronson, 1995).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Also, Sweden is a country with a strong gender equality ideology (SOU 2014;Wahl 1992), and statements that one sex is better than the other is generally frowned upon. However, previous research has shown that it is sufficient to simply be aware that a negative stereotype exists, for stereotyped group members to subsequently suffer from stereotype threat, which may disrupt their individual performance assessments (Steele 1997;Tellhed and Adolfsson 2017).…”
Section: Interest and Self-efficacymentioning
confidence: 99%
“…It has, for example, been found that when primed with female-stereotypical skills, men's ability decreased (Koenig & Eagly, 2005;Kray et al, 2002). Tellhed and Adolfsson (2018) found that both men and women were affected in the same way under stereotype threat, decreasing the relationship between actual performance on an academic test and their assessment of their performance. A German study (Latsch & Hannover, 2014) investigated the impact of medial portrayals of boys as academic failures, and found that it decreased boys' performance and increased girls'.…”
Section: Introductionmentioning
confidence: 99%